Evaluation of the in vitro susceptibility of clinical isolates of NDM-producing Klebsiella pneumoniae to new antibiotics included in a treatment regimen for infections - Słabisz, Natalia; Leśnik, Patrycja; Janc, Jarosław; Fidut, Miłosz; Bartoszewicz, Marzenna; Dudek-Wicher, Ruth; Nawrot, Urszula (Frontiers in Microbiology, 2024)
Background: Due to the growing resistance to routinely used antibiotics, the search for new antibiotics or their combinations with effective inhibitors against multidrug-resistant microorganisms is ongoing. In our study, we assessed the in vitro drug susceptibility of Klebsiella pneumoniae strains producing New Delhi metallo-β-lactamases (NDM) to antibiotics included in the Infectious Diseases Society of America (IDSA) and European Society of Clinical Microbiology and Infectious Diseases (ESCMID) recommendations. Methods: A total of 60 strains of NDM-producing K. pneumoniae were obtained from different patients hospitalized at the 4th Military Hospital in Wroclaw between 2019 and 2022 and subjected to drug susceptibility to selected antibiotics, including the effects of drug combinations. Results: Among the tested antibiotics, the highest sensitivity (100%) was observed for cefiderocol, eravacycline (interpreted according to the European Committee on Antimicrobial Susceptibility Testing, EUCAST), and tigecycline. Sensitivity to intravenous fosfomycin varied depending on the method used. Using the "strip stacking" method, determining cumulative sensitivity to ceftazidime/avibactam and aztreonam demonstrated 100% in vitro sensitivity to this combination among the tested strains.The in vitro susceptibility assessment demonstrated that, the best therapeutic option for treating infections caused by carbapenemase-producing strains seems to be a combination of ceftazidime/avibactam with aztreonam. Due to the safety of using both drugs, cost effectiveness, and the broadest indications for use among the tested antibiotics, this therapy should be the firstline treatment for carbapenemase-producing Enterobacterales infections. Nevertheless, a comprehensive evaluation of the efficacy of treating infections caused by NDM-producing Klebsiella pneumoniae strains should include not only in vitro susceptibility assessment but also an analysis of clinical cases.